The Influence of Satisfaction , Variety Seeking and Alternative Attractiveness to Switching Behaviour Through Switching Intentions - Hartono, Kundi; Wahyono, Wahyono (Universitas Negeri Semarang, 2018)
The purpose of this study was to examine the direct effect of satisfaction, variety seeking and alternative attractiveness on switching behavior through switching intentions. The population in this study are visitors to the CafÃ© Sisemoet Ungaran in May 2018. The technique of sampling used was incidental sampling with 115 respondents. The data collection included questionnaires, documentation, and path analysis as the method of the data analysis. Data analysis is done by using partial test and path analysis test with help of SPSS 21 for Windows.The results showed that satisfaction has direct effect negatively and significantly toward switching behavior, while variety seeking and attractiveness alternatives have a positive and significant direct influence on switching behavior. The results of path analysis test proved that satisfaction, variety seeking, and attractiveness alternatives have indirect effect toward switching behavior through switching intentions.